2020
DOI: 10.1177/0033294120968080
|View full text |Cite
|
Sign up to set email alerts
|

Switch Off Totally or Switch Off Strategically? The Consequences of Thinking About Work on Job Performance

Abstract: As a universal workplace phenomenon, the impact of work-related rumination on job performance is attracting scholars’ attention. In the current study, the relationship between two types of work-related rumination, counterproductive behavior, and creativity at work were examined, as well as the mechanism of this association. Participants were 1109 employees from a variety of jobs in mainland China. The results showed that affective rumination was negatively associated with employees’ work creativity and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 41 publications
0
27
0
3
Order By: Relevance
“…Interestingly, of the 25 studies revised, only seven studies used the complete WRRS and those included the original study in which the WRRS was developed ( Cropley et al, 2012 ; Querstret and Cropley, 2012 ; Vandevala et al, 2017 ; Dunn and Sensky, 2018 ; Sulak Akyüz and Sulak, 2019 ; Weigelt et al, 2019a ; Mullen et al, 2020 ), 11 used the affective and problem-solving pondering subscales ( Bisht, 2017 ; Kinnunen et al, 2017 , 2019 ; Querstret et al, 2017 ; Syrek et al, 2017 ; Vahle-Hinz et al, 2017 ; Firoozabadi et al, 2018a , b ; Junker et al, 2020 ; Zhang et al, 2020 ; Pauli and Lang, 2021 ), two studies used the problem-solving pondering and Detachment subscales ( Zoupanou et al, 2013 ; Mehmood and Hamstra, 2021 ), only one used the Detachment subscale ( Svetieva et al, 2017 ), and four studies used the affective rumination subscale ( Querstret et al, 2016 ; Van Laethem et al, 2019 ; Weigelt et al, 2019b ; Cropley and Collis, 2020 ; Smyth et al, 2020 ). Thus, the use of the subscales of the WRRS vary according to the researchers need and purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, of the 25 studies revised, only seven studies used the complete WRRS and those included the original study in which the WRRS was developed ( Cropley et al, 2012 ; Querstret and Cropley, 2012 ; Vandevala et al, 2017 ; Dunn and Sensky, 2018 ; Sulak Akyüz and Sulak, 2019 ; Weigelt et al, 2019a ; Mullen et al, 2020 ), 11 used the affective and problem-solving pondering subscales ( Bisht, 2017 ; Kinnunen et al, 2017 , 2019 ; Querstret et al, 2017 ; Syrek et al, 2017 ; Vahle-Hinz et al, 2017 ; Firoozabadi et al, 2018a , b ; Junker et al, 2020 ; Zhang et al, 2020 ; Pauli and Lang, 2021 ), two studies used the problem-solving pondering and Detachment subscales ( Zoupanou et al, 2013 ; Mehmood and Hamstra, 2021 ), only one used the Detachment subscale ( Svetieva et al, 2017 ), and four studies used the affective rumination subscale ( Querstret et al, 2016 ; Van Laethem et al, 2019 ; Weigelt et al, 2019b ; Cropley and Collis, 2020 ; Smyth et al, 2020 ). Thus, the use of the subscales of the WRRS vary according to the researchers need and purpose.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study confirmed that affective rumination is significantly negatively correlated with creativity, while problem-solving pondering is significantly positively correlated with creativity [ 25 ]. On this basis, the following was predicted:…”
Section: Introductionmentioning
confidence: 57%
“…The content of affective rumination focuses on the negative emotional experience of work experience [ 24 ]. When affective rumination occurs, individuals perceive work as uncontrollable, and there is inevitable stress [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, rumination predicts both SWB and SIB: "rumination→SWB" [25,26], "rumination→SIB" [27]. Rumination also predicts presenteeism, and SCI predicts SWB and SIB: "rumination→presenteeism" [44,45], "SCI→SWB" [31], and "SCI→SIB" [32,33]. Hence, regarding the"rumination→SCI→presenteeism→SWB and SIB" models, the direct effects on our path models were shown in these previous studies.…”
Section: Introductionmentioning
confidence: 81%